The Short-Term Impacts of a Schooling Conditional Cash Transfer Program on the Sexual Behavior of Young Women - Baird, Sarah; Chirwa, Ephraim; McIntosh, Craig; Ozler, Berk (2012)
Recent evidence suggests that conditional cash transfer (CCT) programs for schooling are effective in raising school enrolment and attendance. However, there is also reason to believe that such programs can affect other outcomes, such as the sexual behavior of their young beneficiaries. Zomba Cash Transfer Program is a randomized ongoing CCT intervention targeting young women in Malawi that provides incentives (in the form of school fees and cash transfers) to current schoolgirls and recent dropouts to stay in or return to school. An average offer of US$ 10/month conditional on satisfactory school attendance--plus direct payment of secondary school fees--led to significant declines in early marriage, teenage pregnancy, and self-reported sexual activity among program beneficiaries after just one year of program implementation. For program beneficiaries who were out of school at baseline, the probability of getting married and becoming pregnant declined by more than 40 and 30%, respectively. In addition, the incidence of the onset of sexual activity was 38% lower among all program beneficiaries than the control group. Overall, these results suggest that CCT programs not only serve as useful tools for improving school attendance but may also reduce sexual activity, teen pregnancy, and early marriage.